Kondisi Keuangan, Pertumbuhan Perusahaan, Dan Profitabilitas Terhadap Penerimaan Opini Going Concern Pada Perusahaan Rokok Yang Terdaftar Di BEI Periode 2019-2021 - Hidayati, Fitri; Solikah, Mar’atus; Sugeng (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
Uncertain economic conditions force investors to take a lot of consideration in investing, so that the presentation of relevant information to users of financial statements regarding going concern audit opinions is very important to make business decisions more precise. This research was conducted with the aim of knowing the factors that influence the Going Concern Opinion. The method used in this study is Iogistic regression. The results of the study prove that partialIy the company's growth has a significant effect on the acceptance of going concern opinions, the company's financiaI condition and profitabiIity have no significant effect on the acceptance of going concern opinions, and simuItaneousIy the company's financiaI conditions, company growth, and profitabiIity have a significant effect on the acceptance of going concern opinions on food and beverage companies Iisted on the lndonesia Stock Exchange in 2019-2021